ANALYSIS OF THE IMPACTS OF BILATERAL FREE TRADE AGREEMENT BETWEEN INDONESIA AND AUSTRALIA - Hakim, Dimal (The Graduate School, Ajou University, 2010)
Since the establishment of the World Trade Organization (WTO) on January 1st, 1995, member countries are committed to adopt all the agreed provisions of the new trading system under the principles of non-discrimination and transparency. The idea was to have a fairer trading system and also to promote trade liberalization among member countries by reducing or eliminating all trade distorting policies. Nevertheless, the failure of the WTO Ministerial Conferences (Doha Round in 2001) has been hampering the development of a Multilateral Trading System. Because of that, many countries have been considering creating Bilateral and Regional Free Trade Agreements (FTA). One of the most potential bilateral FTA for Indonesia is the Australia because Australia is a potential partner which currently ranks eighth as export destination and seventh as import destination. The research objectives for this thesis are to estimate the impact of tariff and Trade Investment Framework (TIF) to total trade, total export and total import between Indonesia and the Australia. The econometric models are used to measure the possible impact of total trade, total export and total import with Time Series (OLS) data between Indonesia and Australia using over the period of 1980-2008 with quarterly data. Normality test, Durbin Watson test (auto correlation) and White - heteroskedasticity test with cross terms are conducted for time series data. We have created three economic models, done some regressions and deeply analyzed the outcomes. Here are some highlighted insights: - Dummy variable TIF has insignificant impact on any of our dependent variables？total trade, export, and import. It indicates that the TIF establishment at 2005 still has no impact on the trade between Indonesia and Australia. - Speaking of Indonesian tariff, it shows insignificant impact at 5% significance level to total trade between Indonesia and Australia. The same goes with the impact of Indonesian tariff to Indonesia export to Australia. Indonesia tariff has insignificant impact even at 10% significance level to Indonesia import from Australia. Therefore, based on Indonesia tariff analysis, the change of Indonesia tariff has no impact on the trade between Indonesia and Australia. - In terms of Australian tariff, it has significant impact and negative relation to total trade between Indonesia and Australia, which logically implies that the decrease of Australian tariff for Indonesia commodities can increase the total trade volume between Indonesia and Australia. Based on Australian tariff analysis, the decrease of the Australian tariff on Indonesian commodities can give a significant benefit to both countries. Based on the above insights, we conclude that even though decreasing of Australia tariff can have a good effect on the total trade between Indonesia and Australia, generally there is still no significant impact caused by the present TIF agreement, at least up to 2008. Therefore, we suggest the Government of Indonesia reconsider the free-trade policy with Australia. We also recommend that the Government of Indonesia approach Australia about decreasing or even removing Non Tariff Barriers (NTB). Other than decreasing the tariff, removing NTB could be effective to increase Indonesia exports to Australia.
학위논문(석사)--아주대학교 국제대학원--국제통상학과,2010. 4
Keywords: international trade